H-function with complex parameters II: evaluation - Fadhel A. Al-Musallam; Vu Kim Tuan (International Journal of Mathematics and Mathematical Sciences)
Sufficient conditions for computation of the H-functions with complex parameters by means of residues are derived and some examples are given.